Trace Elements and Ferritin in Pig Saliva: Variations during Fattening, Time of Sampling, Effect of Dirtiness and Stability under Different Storage Conditions - Alba Ortín-Bustillo; Damián Escribano; Silvia Martínez-Subiela; Asta Tvarijonaviciute; Alberto Muñoz-Prieto; Marina López-Arjona; José J. Cerón; Fernando Tecles (MDPI AG, 2023)
The objective of this study was to evaluate the possible changes of zinc (Zn), copper (Cu), iron (Fe) and ferritin during the entire productive cycle in fattening pigs and at different diurnal sampling times. Moreover, the possible effects of the presence of pen contaminants and storage stability at different temperature conditions were assessed. The analytes changed along the different phases of the fattening productive cycle, showing, in general, higher values at the initial phases. In addition, statistically significant variations were found in Zn and Cu measurements at different sampling times of the day. In the spectrophotometric assays, the values of all analytes significantly increased after adding high concentrations of feces or feed. However, when low concentrations of feces or feed were added, only Cu showed a significant increase. Overall, the salivary levels of Zn, Cu, Fe and ferritin in pigs can change during different fattening phases and the different hours of the day. These analytes were more stable at −80 °C and, if saliva is contaminated with feces or feed, it can lead to an increase in these analytes.